(untitled) (Journal of Business Management and Accounting, 2016)
Global warming, manmade pollution, and pressure from various stakeholders are among the factors that drive business organisations to strike a balance in their operations by reducing negative impact on the environment and society, while increasing the company’s wealth. In response to these pressures, one common method is voluntary disclosure of information on environmental impact through publication of corporate social responsibility report. The majority of studies on company’s environmental issues primarily look from the external viewpoint. This paper takes an alternative approach focusing on processes in relation to the management of environmental issues. Among the areas explored are pressure factors that lead managers to adopting sustainability management, the types of environmental information being considered, its usage, and the users. The findings derived from interviews with several key personnel revealed that a number of external and internal pressures lead to a variety of internal users from different departments in the organisation.